LAYANANIBADAH QURBANMASAPANDEMICOVID-19 DI MASJID DAARUL MUHAJIR KEC. MARGAASIH KAB. BANDUNG - Abdur Rahmanesa; Cahyadi Supyansuri (NIAGARA Scientific Journal, 2022)
One of the big days of the Islamic community is Eid al-Adha and it is recommended by Shari'ah that the community witness it together as a symbol of Islam. Worship on Eid al-Adha after carrying out sunnah prayers is the Sacrifice Worship, namely slaughtering Qurban animals. This Qurban service refers to the event of Prophet Ibrahim as a test by Allah for his love by sacrificing his son, Prophet Ismail.The understanding of the general public that the Quban worship is carried out in turns, for example, is represented by si-Pulan as the head of the family, next year represented by his wife, then represented by his son. Based on the history of the Prophet Muhammad Shallallahu'alaihi Wasallam, he never took turns to his wives and was sufficiently represented by him for the family. The Companions of the Prophet as the head of the family did not also take it in turns to offer qurbani to their wives and children.Sacrificial animals that are slaughtered are generally cows and goats, where for one cow seven people and one goat for one person. During the last two years during the Covid-19 pandemic, research results based on the dimensions of service quality were 61.8% better than the two years before the Covid-19 pandemic. An average of 12.5 cows for sacrifice were slaughtered before the Covid-19 pandemic, which took around 10 hours to complete. During the two years of the Covid-19 pandemic and implementing the health protocol policy, the number of sacrificial animals slaughtered was an average of 12 heads with an implementation time of around 7 hours, 3 hours faster or in other words 30% faster than before during the Covid-19 pandemic.